Effect of motivation, leadership, and work discipline on employees’ performance (Case study of PT. Injakayu Terpadu, Gunung Putri - Bogor) - Hakim .; Rahmat Alhakim (STIE Binaniaga, 2020)
Motivation, leadership and workplace discipline are three of several factors that are regarded to have relatively great influence on the performance of employees of PT Integrated Injakayu Terpadu, Gunung Putri Bogor. To investigate the effect, the present research aimed to determine the influence of motivation, leadership and working discipline on the performance of the employees of the company. The study was conducted by taking 70 employees as a research sample which was an proportional to a total population of 230 employees. Data were collected using a closed questionnaire instrument with six rating scales ranging from very poor/low to very good/excellent. This quantitative study was conducted by describing research data and conducting analysis on the inference. Multiple linear regression analysis and multiple determination coefficients were used for analysis while hypothesis testing was done by the F-test and t-test. This study produces a robust model which shows the influence of motivation, leadership and workplace discipline on employee performance indicated by the multiple linear regression equation Ŷ = 0.167 + 0.940X1 + 0.008X2 + 0.035X3. The correlation coefficient is R = 0.957 which shows that motivation, leadership and work discipline are strongly related to the employee’s performance. Adjusted R2 value = 0.912 shows that motivation, leadership and workplace discipline in the model are simultaneously able to explain 91.2% employee performance variable of PT Injakayu Terpadu, Gunung Putri Bogor, while 8.8% other variable explained not examined in this study. The three main findings revealed in this study are consistent with the proposed hypotheses, i.e. motivation has a positive and significant effect on employee performance, leadership has no effect on employee performance, and workplace discipline does not affect employee performance. Keywords: Motivation, Leadership, Workplace Discipline, and Performance